Character Formation of Anak Sasian in Silek Pauh at Singo Barantai Lubuk Lintah, Kuranji District, Padang City - Syafitri, Mahdalena; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to describe and discuss the Character Formation of Sasian Children in Silek Pauh at the Singo Barantai Lubuk Lintah College, Kuranji District, Padang City. This research method uses a type of qualitative research with a descriptive analysis approach. The main instrument in this study was the researcher himself who was assisted with supporting tools such as cellphones, stationery and cameras. Types of data using primary data and secondary data. The informants in this study were silek teachers and sasian children. Data collection techniques were carried out by means of literature study, observation, interviews and documentation. Techniques for analyzing data use steps in the form of data collection, data reduction, data presentation and verification/conclusion. The results of this study reveal that the formation of the character of the sasian children in silek pauh at Singo Banantai college is through a training method and process in which the teacher/trainer explains the relationship between philosophy and adap in the basilek and the relationship between the attitude of motion and the philosophy of silek movement, in addition, the process of forming the character of the sasian child starting from the process of arrival of the children until the completion of training. From the training process there are several characters that must be instilled in Sasian children, namely fair, honest, polite and civilized, sporty, tough and courageous, responsible and respectful. With the formation of the character of Sasian children, they can form generations that are useful for both the family environment, society and the country.